2015
DOI: 10.5505/tjtes.2015.05046
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Scoring Systems Predicting Mortality in Geriatric Emergency Abdominal Surgery

Abstract: BACKGROUND: Accurate measurement of surgical outcomes, proper evaluation of hospitals and surgeons regardless of case can be performed by mortality prediction models. The aim of this study was to analyze factors affecting mortality, present our clinical experience and patient profile and evaluate different scoring systems in use of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, there seems to be no consensus as to the reliability of this score in predicting mortality in clinical practice. While several studies have shown that P-POSSUM is an accurate indicator of mortality (Gonzalez-Martinez et al 2016, Hayes et al 2016, Igari et al 2013, Tyagi et al 2017), it has also been seen that it can over predict mortality (Ozban et al 2015, Stonelake et al 2015). There have been multiple studies exploring the effectiveness of P-POSSUM in determining mortality risk in general surgical patients with a particular focus in evaluating the risk in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…However, there seems to be no consensus as to the reliability of this score in predicting mortality in clinical practice. While several studies have shown that P-POSSUM is an accurate indicator of mortality (Gonzalez-Martinez et al 2016, Hayes et al 2016, Igari et al 2013, Tyagi et al 2017), it has also been seen that it can over predict mortality (Ozban et al 2015, Stonelake et al 2015). There have been multiple studies exploring the effectiveness of P-POSSUM in determining mortality risk in general surgical patients with a particular focus in evaluating the risk in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are recent studies that compared a number of available frailty scores. In one study, the diagnostic accuracy of six screening instruments for frailty was evaluated.…”
Section: Screening and Assessment Of Frailtymentioning
confidence: 99%
“…A second study used scoring systems developed for intensive care medicine and elective surgery, and analysed whether they could predict mortality in the frail elderly patient needing emergency surgery. The scoring systems varied in terms of sensitivity and estimated mortality, but the Acute Physiology And Chronic Health Evaluation (APACHE) II system had a sensitivity of 96 per cent in estimating postoperative mortality.…”
Section: Screening and Assessment Of Frailtymentioning
confidence: 99%
“…In our study the higher risk groups were predicted better with lower risk groups having overprediction. Ozman M et al 10 in their study concluded that POSSUM scoring obtained from a heterogeneous population was a successful audit tool, but in low risk groups, it overestimated the mortality rate. Moreover they reported that predictive value of POSSUM for morbidity was affected by the type of surgery and the sample size of the study.…”
Section: Discussionmentioning
confidence: 99%